The Impact of Emotional Intelligence on Academic Achievements of Students at University of Mianwali: https://doi.org/10.5281/zenodo.17002569 - Sehrish Naseer, PhD; Dr. Sajjad Haider Adv; Rahat Yasmeen, PhD (Corresponding Author) (`, 2025)
The main goal of the current study was to examine “The impact of emotional intelligence on academic achievements of students at university level”. The nature of the current study was quantitative and correlational research design was applied. University of Mianwali was selected as population of the study and undergraduate students of university of Mianwali, was selected as targeted population. The sample will include from four departments (Department of Urdu, Department of English) from faculty of arts and humanities and ( Department of Psychology and Department of Education) from faculty of social sciences. The sample was selected through simple random sampling. The sample included 400 students from the above-mentioned departments’ regular and self-support programs; B.S (2nd, 6th and 8th semester). An adopted questionnaire of Wong and law Emotional Intelligence Scale WLIES developed by Wong & Law (2002) was used. Academic achievements was measured through students CGPA. Data was collected by using both means online through Google forms. Data were analyzed through inferential statistics (correlation and t test) with the help of Statistical Package for Social Sciences (SPSS). Pearson correlation coefficient showed an insignificant relationship between emotional intelligence and academic achievements of the respondents. The difference between male and female emotional intelligence was insignificant. The difference between male and female emotional intelligence was also insignificant. It was recommended on the basis of the results that universities need to conduct seminar and workshop to spread awareness about emotional intelligence so that the mental issues of the students addressed and their academic achievement enhanced. Key words: Emotional Intelligence, Academic Achievement, Students, Mianwali, University